EFFECT OF TRANSFERSOME ON THE STABILITY AND ANTIOXIDANT ACTIVITY OF GLUTATHIONE IN ANTIAGING CREAMS - HARMITA, HARMITA; ISKANDARSYAH; MURTI, FRIAINI ZAHRA (International Journal of Applied Pharmaceutics, 2020)
Objective: Glutathione is an important antioxidant compound that is added to various cosmetic preparations. This study compared the stability, antioxidant activity, and penetration of glutathione creams formulated with and without transfersome, a commonly used carrier system. Methods: The particle size of the transfersome was 55.65 nm, with a polydispersity index of 0.398 and an entrapment efficiency of 66.22%. During cycling and centrifugal testing, the creams (with and without transfersome) did not change color or demonstrate phase separation. Chemical stability analyses of the products were performed using high-performance liquid chromatography. Results: The remaining glutathione content in the transfersome cream was 83.44%, while that of the non-transfersome cream was 47.92%. In the penetration test using Franz diffusion cells, the transfersome cream demonstrated a cumulative penetration of 4474.44 μg/cm2, with a cumulative concentration percentage of 39.60% and a flux of 510.38 μg/cm−2h−1. In contrast, the non-transfersome cream demonstrated a cumulative penetration amount of 2793.80 μg/cm2, with a cumulative concentration percentage of 24.73% and a flux of 340.12 μg/cm−2h−1. In addition, the IC50 value of the transfersome cream preparation was 11.89 μg/mL, while that of the non-transfersome preparation was 15.57 μg/mL. Conclusion: Our findings indicate that the use of transfersome increases the stability and penetration of glutathione in cream preparations.